Ceramic tile and preparation method thereof

By adding ceramic waste ink to the raw material of ceramic tiles, the problem that ceramic waste ink cannot be recycled is solved, realizing resource conservation and sustainable development of ceramic products.

CN119349986APending Publication Date: 2025-01-24DONGGUAN CITY WONDERFUL CERAMICS IND PARK +1

Patent Information

Application Number
CN202411484775.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art causes serious waste of resources due to the inability to recycle ceramic waste ink.

Method used

Add ceramic waste ink to the raw material of ceramic tiles, and prepare recyclable ceramics by mixed with raw mud, stone powder raw materials, medium temperature sand raw materials, magnesium soil, water glass, and F-02 dispersers.

Benefits of technology

The recycling of ceramic waste ink is realized, the cost of production and processing of waste ink is saved, the waste of resources is avoided, and the internal quality and sustainable development of ceramic products are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349986A_ABST
    Figure CN119349986A_ABST
Patent Text Reader

Abstract

The invention provides a ceramic tile and a preparation method thereof, the green body of the ceramic tile comprises the following raw materials by mass: 30%-35% of raw slime, 33%-38% of a stone powder raw material, 23%-28% of a medium temperature sand raw material, 2%-4% of magnesia soil, 0.1%-0.2% of ceramic waste ink, 0.8%-1.0% of water glass, and 0.06%-0.1% of an F-02 dispersant. According to the invention, the ceramic waste ink is added into the formula of the green body, so that the recycling of the waste ink is realized, the production cost is saved, the cost for treating the waste ink is saved, and the problem of serious resource waste caused by incapability of recycling the ceramic waste ink is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic production, and in particular to a ceramic brick and a preparation method thereof. Background Art

[0002] The emergence of ceramic inkjet printing machines has set off a climax in ceramic inkjet printing. Inkjet printing technology is currently a more advanced printing technology in the ceramic industry. However, the cost of using inkjet technology is still quite high at this stage.

[0003] At present, the waste ink generated by the ceramic inkjet printing machines of most ceramic enterprises during the production process is collected in the waste ink barrel for disposal and cannot be recycled; some manufacturers set up pipes for each nozzle when designing the equipment, and directly recycle it into the original ink barrel, but there are problems such as unstable printing, easy to have problems such as pulling lines (blocking nozzles) and streaks (discoloration of a single nozzle, no spraying). In the production process of ceramic inkjet printing, in order to prevent nozzle blockage, the nozzle usually needs to be flushed with ink every 3 to 4 hours. If dark products are produced, the frequency of flushing the nozzle will be even higher. According to incomplete statistics, an inkjet printing machine generates about 2kg of waste ink a day. Based on the current average price of ceramic ink of 50 to 80 yuan / kg, an inkjet printing machine wastes about 50,000 yuan of ink a year. Therefore, the inability to recycle ceramic waste ink has caused serious waste of resources.

[0004] Therefore, the prior art has defects and needs to be improved and developed. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a ceramic tile and a preparation method thereof in view of the above-mentioned defects of the prior art, aiming to solve the problem of serious waste of resources caused by the inability to recycle ceramic waste ink in the prior art.

[0006] The technical solution adopted by the present invention to solve the technical problem is as follows:

[0007] In a first aspect of the present application, an embodiment provides a ceramic tile, wherein the green body raw materials of the ceramic tile include, by mass percentage:

[0008] 30% to 35% of original ore mud, 33% to 38% of stone powder raw materials, 23% to 28% of medium-temperature sand raw materials, 2% to 4% of magnesia soil, 0.1% to 0.2% of ceramic waste ink, 0.8% to 1.0% of water glass, and 0.06% to 0.1% of F-02 dispersant.

[0009] In one embodiment of the present application, the ceramic waste ink includes: ceramic powder, water-soluble organic solvent, dispersant, binder and surfactant.

[0010] In one embodiment of the present application, the ceramic powder includes pigments, colorants and glazes.

[0011] In one embodiment of the present application, the ceramic waste ink is generated by an inkjet printing machine during the ceramic production process.

[0012] In one embodiment of the present application, the ceramic waste ink is obtained by filtering impurities from waste ink produced by an inkjet printer in a ceramic production process using a 70-80 mesh screen.

[0013] A second aspect of the present application provides a method for preparing a ceramic tile, wherein the method comprises:

[0014] According to the mass percentage, 30% to 35% of raw ore mud, 33% to 38% of stone powder raw materials, 23% to 28% of medium-temperature sand raw materials, 2% to 4% of magnesia soil, 0.1% to 0.2% of ceramic waste ink, 0.8% to 1.0% of water glass, and 0.06% to 0.1% of F-02 dispersant are mixed to prepare mud, wherein the ceramic waste ink is produced by an inkjet printing machine in the ceramic production process;

[0015] The slurry is screened, iron-removed and aged, and then pumped into a spray tower for powder spraying and drying to obtain ceramic powder; the ceramic powder is screened, iron-removed and aged, and then pressed into shape to obtain a ceramic green body;

[0016] Drying the ceramic green body in a drying kiln, and glazing the dried ceramic green body to obtain a glazed semi-finished green body;

[0017] The semi-finished green body is fired to obtain a ceramic tile.

[0018] In one embodiment of the present application, the moisture content of the mud is controlled at 33% to 36%, the fineness of the mud is controlled at 2.0% to 2.4% on a 325-mesh sieve, and the specific gravity of the mud is ≥1.68 g / mL.

[0019] In one embodiment of the present application, the slurry is screened, iron-removed, and aged, and then pumped into a spray tower for powder spraying and drying to obtain a ceramic powder. The ceramic powder is screened, iron-removed, and aged, and then pressed into a shape to obtain a ceramic green body, including:

[0020] The slurry is passed through a 70-80 mesh sieve, iron removed, and aged, and then pumped into a spray tower for powder spraying and drying to obtain a ceramic powder with a moisture content of 6.8% to 7.3%, wherein the ceramic powder has a 40 mesh particle size distribution accounting for 45% to 50%;

[0021] The ceramic powder is passed through a 10-16 mesh sieve, subjected to iron removal and aging treatment, and then fed into a press material distribution system through a powder feeding system for compression molding at a molding pressure of 30-32 MPa to obtain a ceramic green body.

[0022] In one embodiment of the present application, the ceramic green body is dried in a drying kiln, and the dried ceramic green body is glazed to obtain a glazed semi-finished green body, comprising:

[0023] The ceramic green body is dried in a drying kiln at a temperature of 100 to 120° C. for 50 to 60 minutes.

[0024] The glaze slurry is applied on the dried ceramic green body by pouring glaze, and the performance parameters of the glaze slurry include: fineness of 325 mesh sieve residue is 0.2% to 0.4%, glaze slurry viscosity is 25 to 35 seconds, specific gravity is 1.7 to 1.8 g / mL, glaze amount is 500 to 550 g / m 2 ;

[0025] The chemical components of the glaze slurry, measured by mass percentage, include:

[0026] SiO2 43% to 49%, Al2O3 15% to 17%, CaO 3% to 6%, MgO 2% to 4%, BaO3% to 6%, K2O 1% to 2%, Na2O 2% to 4%, ZnO 2% to 4%, ZrO2 5% to 10%.

[0027] In one embodiment of the present application, the semi-finished green body is fired to obtain a ceramic tile, comprising:

[0028] The semi-finished green body is fired at a temperature of 1210-1230° C. and a firing period of 40-43 minutes to obtain a ceramic tile.

[0029] The invention discloses a ceramic tile and a preparation method thereof. The raw materials of the ceramic tile body include, by mass percentage, 30% to 35% of raw ore mud, 33% to 38% of stone powder raw materials, 23% to 28% of medium-temperature sand raw materials, 2% to 4% of magnesia soil, 0.1% to 0.2% of ceramic waste ink, 0.8% to 1.0% of water glass, and 0.06% to 0.1% of F-02 dispersant. The invention adds ceramic waste ink to the body formula, realizes the recycling of waste ink, saves both production cost and waste ink treatment cost, and avoids the problem of serious waste of resources caused by the inability to recycle ceramic waste ink. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a flow chart of a preferred embodiment of a method for preparing ceramic tiles in the present invention.

[0031] Figure 2 It is a specific process production block diagram of a preferred embodiment of a ceramic tile preparation method in the present invention. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention clearer and more specific, the present invention is further described in detail below with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] In the embodiment of the present application, waste ink in production is collected and sieved to remove impurities, and an appropriate amount of waste ink is added to the green body formula for processing to prepare ceramic slurry, which not only saves production costs but also is beneficial to environmental protection, contributes to the sustainable and healthy development of the ceramic industry, and has good economic and social benefits.

[0034] The present application provides a ceramic tile, the raw materials of the ceramic tile body, calculated by mass percentage, include: 30% to 35% of original ore mud, 33% to 38% of stone powder raw materials, 23% to 28% of medium-temperature sand raw materials, 2% to 4% of magnesia soil, 0.1% to 0.2% of ceramic waste ink, 0.8% to 1.0% of water glass, and 0.06% to 0.1% of F-02 dispersant.

[0035] Specifically, the raw ore mud, as the main component of the ceramic tile body, provides the necessary plasticity and forming properties, and the high content of the raw ore mud helps to form a strong body structure. The raw ore mud can be kaolin, which is a common ceramic raw material, the main components of which are silicon dioxide and aluminum oxide, and have good plasticity and sintering properties.

[0036] Stone powder raw materials can increase the hardness and wear resistance of ceramic tiles. During the high-temperature firing process, stone powder raw materials help to form a stable crystal structure. The stone powder raw materials can be quartz, the main component of quartz is silicon dioxide, which is an inorganic mineral. The stone powder raw materials can also be feldspar, which is a type of stone rich in minerals.

[0037] The addition of medium temperature sand raw materials can adjust the thermal expansion coefficient of the green body, reduce the risk of cracking during the firing process, and improve the thermal shock resistance of the ceramic tile. The medium temperature sand raw material can be medium temperature sand kaolin.

[0038] Magnesia soil helps to improve the strength and toughness of ceramic tiles, and can promote the formation of a stable quaternary phase formula system of components such as silicon dioxide and magnesium oxide in the body, further enhancing the performance of the body. Magnesia soil can be magnesia clay, which is rich in magnesium and can improve the strength and toughness of ceramic tiles.

[0039] Water glass has good adhesion and water retention, which helps to improve the forming performance and drying strength of the green body, and can also improve the weather resistance and chemical stability of ceramic tiles. Water glass can be a sodium silicate aqueous solution, which can improve the forming performance and drying strength of the green body in the production of ceramic tiles.

[0040] F-02 dispersant can effectively disperse particles in the green body, prevent agglomeration, and help improve the uniformity and density of the green body, thereby improving the overall performance of ceramic tiles. F-02 dispersant, also known as "F02 anti-settling agent", is an environmentally friendly new type of nano hollow spherical functional powder material, and is also a base material for stable clear phase materials.

[0041] The embodiment of the present application adds ceramic waste ink to the blank formula, thereby realizing the recycling of the waste ink, saving both production costs and the cost of treating the waste ink, and avoiding the problem of serious waste of resources caused by the inability to recycle ceramic waste ink.

[0042] In the embodiment of the present application, the ceramic waste ink includes: ceramic powder, water-soluble organic solvent, dispersant, binder and surfactant.

[0043] Specifically, ceramic waste ink contains various organic molecules such as solvents, dispersants, binders, surfactants, etc., which will directly affect the performance of ball mill slurry. By adjusting the addition ratio of water glass and F-02 dispersant in the formula auxiliary materials, the flow rate difference and thixotropy of ball mill slurry can be solved.

[0044] In one embodiment of the present application, the ceramic powder includes pigments, colorants and glazes. Specifically, since ceramic waste ink contains ceramic pigments of various colors, it can be regarded as black pigments. Therefore, it can only be used in low-whiteness green body formulas. If it is used in high-whiteness formulas, the whiteness of the green body in the original formula will be reduced. Due to the increasing shortage of high-quality raw materials and in order to reduce the cost of ceramic production, a large amount of low-priced, poor-quality raw materials are used, which will lead to a high iron content in the ceramic green body formula and a reddish green body color. For example, if a large amount of low-quality raw materials are used in the green body formula of a 20-degree green body with high water absorption, the green body whiteness will be low and the green body color will be reddish-yellow. In the industry, brick green body color is generally considered to be poor in reddish color. Therefore, in order to improve the green body color of brick green body, by adding 0.1% to 0.2% of ceramic waste ink to the green body formula, the green body color of the sintered product is green-yellow, which better improves the problem of the green body of the 20-degree green body with high water absorption.

[0045] In the embodiment of the present application, the ceramic waste ink is produced by an inkjet printer during the ceramic production process. Specifically, the ceramic waste ink produced by the inkjet printer is usually composed of ceramic powder (colorant, colorant, glaze), water-soluble organic solvent, dispersant, binder, surfactant and other auxiliary materials. Generally, the organic parts of ceramic inks of different colors are not much different, and the ceramic powder (colorant, colorant, glaze) is the core material of ceramic ink. Ceramic colorants are minerals for ceramic coloring that are artificially synthesized with transition metals, rare earth metals or other metals as coloring elements and a certain crystal form as a color matrix. Ceramic ink needs to be stably colored when fired at high temperatures. The ceramic colorants in most ceramic inks are mainly spinel and other structural types, and their particle size is less than 1μm. In addition, many oxides in the ceramic colorant raw materials are strong co-solvents, so the firing temperature of ceramic ink is relatively low. By adding 0.1% to 0.2% of ceramic waste ink to the blank formula and adjusting the content of talc or stone powder in the blank formula, the blank firing temperature range can be widened, making the blank easier to sinter, and facilitating the formation and homogenization of mullite crystals in the blank, thereby improving the product's modulus of rupture. The original formula product without adding ceramic waste ink has a modulus of rupture of 45Mpa to 48Mpa, which can be increased to 47Mpa to 52Mpa in the embodiment of the present application.

[0046] In one embodiment of the present application, the ceramic waste ink is obtained by filtering impurities from waste ink produced by an inkjet printer in a ceramic production process using a 70-80 mesh screen.

[0047] The embodiment of the present application collects the waste ink generated in the ceramic production, sieves it to remove impurities, adds an appropriate amount of the filtered waste ink to the green body formula for ball milling, and recycles the waste ink to prepare ceramic slurry, which not only saves production costs and the cost of processing waste ink, but also is beneficial to environmental protection and the sustainable development of the ceramic industry, achieving "zero" emissions of waste and wastewater.

[0048] In the embodiment of the present application, the chemical components of the raw ore mud, calculated by mass percentage, include: SiO2 60%~65%, Al2O3 22%~26%, Fe2O3 1.2%~2.0%, K2O 1.0%~1.5%, and the rest is loss on ignition. The chemical components of the stone powder raw materials, calculated by mass percentage, include: SiO2 70%~75%, Al2O3 13%~15%, Fe2O3 0.5%~1.5%, CaO 0.3%~0.5%, MgO0.5%~1.0%, K2O 3.0%~6.0%, Na2O 6.0%~8.0%, and the rest is loss on ignition. The chemical components of the medium-temperature sand raw materials, calculated by mass percentage, include: SiO2 65%~70%, Al2O3 15%~18% 、Fe2O3 0.5%-1.5%, K2O 2.0%-3.0%, Na2O 2.0%-4.0%, and the rest is loss on ignition. The chemical components of the magnesia soil include, by mass percentage, SiO2 64%-67%, Al2O3 2.2%-2.5%, Fe2O3 1.4%-1.6%, CaO 0.5%-1.0%, MgO 22%-24%, and the rest is loss on ignition.

[0049] Therefore, the present application utilizes the advantage of low firing temperature of ceramic waste ink, and by adjusting the low-temperature stone powder raw materials and flux raw materials in the formula, it helps to quickly sinter the green body, increase the rupture modulus of the green body, and improve the brick shape of the product; utilizes various pigments and colorants mixed in ceramic waste ink to solve the problem of reddish green color of products with high water absorption rate; adjusts the green body formula auxiliary material disintegrator to solve the problems of poor mud flow rate and large thixotropy caused by waste ink.

[0050] See also Figure 1 , Figure 1 1 is a flow chart of the method for preparing ceramic tiles in the present invention. Figure 1 As shown, the following steps are included:

[0051] Step S100, according to mass percentage, 30% to 35% of raw ore mud, 33% to 38% of stone powder raw materials, 23% to 28% of medium-temperature sand raw materials, 2% to 4% of magnesia soil, 0.1% to 0.2% of ceramic waste ink, 0.8% to 1.0% of water glass, and 0.06% to 0.1% of F-02 dispersant are mixed to prepare mud, wherein the ceramic waste ink is generated by an inkjet printing machine in a ceramic production process;

[0052] Step S200, after the slurry is screened, iron-removed and aged, it is pumped into a spray tower for powder spraying and drying to obtain ceramic powder; after the ceramic powder is screened, iron-removed and aged, it is pressed into a shape to obtain a ceramic green body;

[0053] Step S300, drying the ceramic green body in a drying kiln, and glazing the dried ceramic green body to obtain a glazed semi-finished green body;

[0054] Step S400, firing the semi-finished green body to obtain a ceramic tile.

[0055] For specific process production diagram, please refer to Figure 2 The embodiment of the present application adjusts the formula structure, adjusts the production process parameters, and utilizes the advantage of low firing temperature of ceramic waste ink to help the green body to sinter quickly, increase the rupture modulus of the green body, and improve the brick shape of the product.

[0056] In the embodiment of the present application, before step S100, it also includes: collecting the waste ink generated by the inkjet printing machine of each production line into an ink barrel, filtering impurities with a 70-80 mesh screen to obtain ceramic waste ink; putting the ceramic waste ink into a storage tank, and packaging it for standby use.

[0057] Specifically, since most ceramic companies currently collect and process the waste ink generated by inkjet printers in production, and cannot recycle it, the treatment method is difficult and the cost is high, which brings a huge cost burden to ceramic companies. In the embodiment of the present application, the waste ink generated by the inkjet printers of each production line is collected in ink barrels, and various impurities are filtered using a 70-80 mesh screen, and then concentrated into a storage tank, and then divided into barrels of about 25 kg and sent to the raw material ball mill workshop for standby.

[0058] The embodiment of the present application saves the cost of treating the waste ink by centrally collecting the waste ink from ceramic production and then putting it into a raw material ball mill for use.

[0059] In one embodiment of the present application, the moisture content of the mud is controlled at 33% to 36%, the fineness of the mud is controlled at 2.0% to 2.4% on a 325 mesh sieve, the specific gravity of the mud is ≥1.68 g / mL, and the flow rate of the mud is 70 to 130 seconds (measured using a 100 ml volume of LND-1 coated four cups).

[0060] Specifically, the embodiment of the present application controls the moisture content of the mud at 33% to 36%, which can make the mud have good fluidity and plasticity during pressing and molding, which is beneficial to the uniform pressing of the ceramic green body and reduces the occurrence of defects such as cracks and deformation; it can also speed up the drying speed of the mud in the drying kiln, shorten the production cycle, improve production efficiency, and thereby reduce energy consumption in the drying process and reduce production costs.

[0061] In the embodiment of the present application, the fineness of the mud is controlled at 2.0% to 2.4% of the 325 mesh residue, so that the mud can form a denser ceramic structure during the firing process, thereby improving the hardness and wear resistance of the product, and making the ceramic tiles more delicate and realistic.

[0062] In the embodiment of the present application, the specific gravity of the mud is controlled to be 1.68 g / mL or above to ensure that the mud has sufficient density and strength during pressing and molding, which is beneficial to improving the overall quality and performance of the ceramic tile. Since too low or too high a specific gravity may cause defects such as deformation and cracking of the ceramic tile during the firing process, controlling the specific gravity can reduce the scrap rate and improve production efficiency.

[0063] The embodiment of the present application controls the flow rate of the mud to 70 to 130 seconds to ensure the stability of the mud during transportation and pressing, which is conducive to improving production efficiency. Too fast a flow rate may cause increased equipment wear, while too slow a flow rate may affect production efficiency. Therefore, controlling the flow rate can reduce equipment wear and extend the service life of the equipment.

[0064] In one embodiment of the present application, step S200 is specifically as follows:

[0065] Step S210, the slurry is passed through a 70-80 mesh sieve, iron removed, aged, and then pumped into a spray tower for powder spraying and drying to obtain a ceramic powder with a moisture content of 6.8% to 7.3%, wherein the ceramic powder has a 40 mesh particle size distribution of 45% to 50%;

[0066] Step S220, after the ceramic powder is sieved through a 10-16 mesh screen, iron removed, and aged, the ceramic powder is fed into a press feeding system through a powder feeding system for compression molding at a molding pressure of 30-32 MPa to obtain a ceramic green body.

[0067] Specifically, after the ball mill slurry is batched and aged for 24 hours in the slurry pool, it is pumped into the spray tower for powder spraying and drying to obtain a powder with a moisture content of 6.8% to 7.3%, and the powder particle size of 40 mesh accounts for 45% to 50%. The ceramic powder is sieved through a 10-16 mesh sieve and iron is removed, and then aged again for 24 hours in the warehouse. According to actual production needs, the powder is sent to the press distribution system for pressing through the powder feeding system, and the molding pressure is 30-32Mpa.

[0068] The mud is passed through a 70-80 mesh sieve to remove larger particles and impurities, making the particle distribution of the mud more uniform, which helps to form ceramic powder with appropriate particle size in the subsequent powder spraying and drying process. The iron removal treatment can remove iron impurities in the mud and avoid defects such as iron spots during the firing process. That is, the embodiment of the present application passes the mud through a 70-80 mesh sieve and removes iron to reduce defects such as bulging, caves and spot impurities in the green body caused by coarse quartz particles, iron impurities, etc. in the mud.

[0069] Aging treatment helps to further evenly distribute the moisture and organic matter in the mud and improve the plasticity of the mud. Pumping into the spray tower for powder spray drying can obtain ceramic powder with a moisture content of 6.8% to 7.3%, which is conducive to the subsequent pressing and firing process. The 40-mesh particle size of the ceramic powder accounts for 45% to 50%, which is conducive to forming a denser green body structure during the pressing process.

[0070] The ceramic powder is passed through a 10-16 mesh sieve to remove larger particles and impurities, ensuring the uniformity of the powder. Iron removal is then performed again to further reduce the impact of iron impurities. The ceramic powder is fed into the press feeding system through a powder feeding system to achieve automated production and improve production efficiency. The molding pressure is controlled at 30-32Mpa, which can ensure the compactness of the green body and avoid cracking or deformation of the green body caused by excessive pressure.

[0071] In one embodiment of the present application, step S300 specifically includes:

[0072] Step S310, drying the ceramic green body in a drying kiln at a temperature of 100 to 120° C. for 50 to 60 minutes;

[0073] Step S320, applying glaze slurry on the dried ceramic green body by pouring glaze, wherein the performance parameters of the glaze slurry include: fineness of 325 mesh residue of 0.2% to 0.4%, glaze slurry viscosity of 25 to 35 seconds, specific gravity of 1.7 to 1.8 g / mL, glaze application amount of 500 to 550 g / m 2 .

[0074] The chemical components of the glaze slurry, measured by mass percentage, include:

[0075] SiO2 43% to 49%, Al2O3 15% to 17%, CaO 3% to 6%, MgO 2% to 4%, BaO3% to 6%, K2O 1% to 2%, Na2O 2% to 4%, ZnO 2% to 4%, ZrO2 5% to 10%.

[0076] Specifically, drying in a drying kiln at 100-120°C for 50-60 minutes can effectively remove residual moisture in the ceramic green body, which helps to avoid internal stress caused by water evaporation during the firing process, thereby reducing the risk of cracking and deformation. The strength of the ceramic green body after drying will be improved, which is beneficial to the subsequent processing and transportation process. Drying can also make the surface of the green body smoother, which is conducive to the uniform application of the glaze slurry. In addition, the dried green body can be heated more evenly during the firing process, thereby improving the firing efficiency and quality. The glazing method can ensure that the glaze slurry is evenly and continuously applied to the ceramic green body, so as to obtain a smooth and uniform glaze surface. The performance parameters of the glaze slurry (such as fineness, viscosity, specific gravity and glaze application amount) are precisely controlled to further ensure the quality of the glaze surface. Oxides such as SiO2 and Al2O3 in the glaze slurry can improve the transparency and brightness of the glaze surface, while CaO, MgO, etc. can affect the hardness and wear resistance of the glaze surface. The chemical composition in the glaze slurry can also enhance the performance of ceramic products, such as improving stain resistance, corrosion resistance, heat resistance, etc., making ceramic products more suitable for various complex and harsh environmental conditions.

[0077] In one embodiment of the present application, the step S400 is specifically: firing the semi-finished green body at a firing temperature of 1210-1230° C. and a firing period of 40-43 minutes to obtain a ceramic tile.

[0078] Since ceramic waste ink has a complex composition and fineness, it is necessary to reduce the heating rate of the kiln's oxidation decomposition during kiln firing, so that the body has enough time to discharge the gases produced by the oxidation and decomposition of organic matter and carbonates before the glaze begins to melt, avoiding defects such as closed bubbles, caves, and pinholes in the glaze.

[0079] The present invention achieves the following effects:

[0080] First, the present invention not only saves the cost of processing waste ink for enterprises by directly recycling ceramic waste ink, but also improves the quality of ceramic products. More importantly, it plays an important role in ecological environmental protection, contributes to the sustainable and healthy development of the ceramic industry, and has significant economic and social benefits.

[0081] Second, by adjusting the formula structure and production process parameters, and taking advantage of the low firing temperature of ceramic waste ink, it helps to quickly sinter the green body, increase the rupture modulus of the green body, and improve the brick shape of the product.

[0082] Third, the various pigments and colorants in ceramic waste ink were used to solve the problem of reddish color of 20-degree high water absorption products.

[0083] Specific embodiments are listed below for illustration.

[0084] Embodiment 1

[0085] Step A1, according to mass percentage, 32% to 34% of raw ore mud, 35% to 37% of stone powder raw materials, 25% to 27% of medium-temperature sand raw materials, 3% to 4% of magnesia soil, 0.1% to 0.2% of ceramic waste ink, 0.8% to 1.0% of water glass, and 0.06% to 0.1% of F-02 dispersant are mixed to prepare mud, wherein the waste ink is generated by an inkjet printing machine in a ceramic production process;

[0086] The moisture content of the mud is controlled at 34% to 35%, the fineness of the mud is controlled at 2.2% to 2.3% of the residue on a 325-mesh sieve, the specific gravity of the mud is ≥1.68 g / mL, and the flow rate of the mud is 70 to 130 seconds.

[0087] Step A2, the slurry is passed through a 70-80 mesh sieve, iron removed, aged, and then pumped into a spray tower for powder spraying and drying to obtain a ceramic powder with a moisture content of 7.0% to 7.1%, wherein the ceramic powder has a 40 mesh particle size distribution accounting for 45% to 50%;

[0088] Step A3: After the ceramic powder is sieved through a 10-16 mesh screen, iron removed, and aged, the ceramic powder is fed into a press feeding system through a powder feeding system for compression molding at a molding pressure of 30-32 MPa to obtain a ceramic green body.

[0089] Step A4, drying the ceramic green body in a drying kiln at a temperature of 110-115° C. for 55-60 minutes;

[0090] Step A5: applying glaze slurry on the dried ceramic green body by pouring glaze, wherein the performance parameters of the glaze slurry include: fineness of 325 mesh sieve residue of 0.3% to 0.4%, glaze slurry viscosity of 28 to 32 seconds, specific gravity of 1.7 to 1.8 g / mL, glaze application amount of 520 to 530 g / m 2 .

[0091] The chemical components of the glaze slurry, measured by mass percentage, include:

[0092] SiO2 43% to 49%, Al2O3 15% to 17%, CaO 3% to 6%, MgO 2% to 4%, BaO3% to 6%, K2O 1% to 2%, Na2O 2% to 4%, ZnO 2% to 4%, ZrO2 5% to 10%.

[0093] Step A6, firing the semi-finished green body at a temperature of 1210-1230° C. and a firing period of 40-43 minutes to obtain a ceramic tile.

[0094] Embodiment 2

[0095] Step B1, according to the mass percentage, 33% of raw ore mud, 36% of stone powder raw material, 26% of medium temperature sand raw material, 3.8% of magnesia soil, 0.2% of ceramic waste ink, 0.92% of water glass, and 0.08% of F-02 dispersant are mixed to prepare mud, wherein the waste ink is generated by an inkjet printing machine in the ceramic production process;

[0096] The moisture content of the mud is controlled at 34%, the fineness of the mud is controlled at 2.3% on a 325-mesh sieve, the specific gravity of the mud is ≥1.68 g / mL, and the flow rate of the mud is 100 seconds.

[0097] Step B2, the slurry is passed through a 70-80 mesh sieve, iron removed, aged, and then pumped into a spray tower for powder spraying and drying to obtain a ceramic powder with a moisture content of 7.0%, wherein the ceramic powder has a 40 mesh particle size distribution accounting for 45%;

[0098] Step B3: After the ceramic powder is sieved through a 10-16 mesh screen, iron removed, and aged, the ceramic powder is fed into a press feeding system through a powder feeding system for compression molding at a molding pressure of 30 MPa to obtain a ceramic green body.

[0099] Step B4, drying the ceramic green body in a drying kiln at a temperature of 110° C. for 55 minutes;

[0100] Step B5, applying the glaze slurry on the dried ceramic green body by pouring glaze, the performance parameters of the glaze slurry include: fineness of 325 mesh sieve residue of 0.3%, glaze slurry viscosity of 28 seconds, specific gravity of 1.7g / mL, glaze amount of 520g / m 2 .

[0101] The chemical components of the glaze slurry, measured by mass percentage, include:

[0102] SiO2 49%, Al2O3 16%, CaO 6%, MgO 4%, BaO 6%, K2O 2%, Na2O 3%, ZnO 4%, ZrO2 10%.

[0103] Step B6, firing the semi-finished green body at a firing temperature of 1210° C. and a firing period of 40 minutes to obtain a ceramic tile.

[0104] Embodiment 3

[0105] Step C1, according to mass percentage, 35% of raw ore mud, 35.8% of stone powder raw material, 24% of medium-temperature sand raw material, 4% of magnesia soil, 0.1% of ceramic waste ink, 1.0% of water glass, and 0.1% of F-02 dispersant are mixed to prepare mud, wherein the waste ink is generated by an inkjet printing machine in the ceramic production process;

[0106] The moisture content of the mud is controlled at 35%, the fineness of the mud is controlled at 2.3% on a 325-mesh sieve, the specific gravity of the mud is ≥1.68 g / mL, and the flow rate of the mud is 130 seconds.

[0107] Step C2, the slurry is passed through a 70-80 mesh sieve, iron removed, aged, and then pumped into a spray tower for powder spraying and drying to obtain a ceramic powder with a moisture content of 7.1%, wherein the ceramic powder has a 40 mesh particle size distribution accounting for 50%;

[0108] Step C3, after the ceramic powder is sieved through a 10-16 mesh screen, iron removed, and aged, the ceramic powder is fed into a press feeding system through a powder feeding system for compression molding at a molding pressure of 32 MPa to obtain a ceramic green body.

[0109] Step C4, drying the ceramic green body in a drying kiln at a temperature of 115° C. for 60 minutes;

[0110] Step C5, applying the glaze slurry on the dried ceramic green body by pouring glaze, the performance parameters of the glaze slurry include: fineness of 325 mesh sieve residue of 0.4%, glaze slurry viscosity of 32 seconds, specific gravity of 1.8g / mL, glaze amount of 530g / m 2 .

[0111] The chemical components of the glaze slurry, measured by mass percentage, include:

[0112] SiO2 49%, Al2O3 16%, CaO 6%, MgO 4%, BaO 6%, K2O 2%, Na2O 3%, ZnO 4%, ZrO2 10%.

[0113] Step C6, firing the semi-finished green body at a firing temperature of 1230° C. and a firing period of 43 minutes to obtain a ceramic tile.

[0114] The present invention provides a ceramic tile and a method for preparing the ceramic tile. The raw materials of the ceramic tile body include, by mass percentage, 30% to 35% of raw ore mud, 33% to 38% of stone powder raw materials, 23% to 28% of medium-temperature sand raw materials, 2% to 4% of magnesia soil, 0.1% to 0.2% of ceramic waste ink, 0.8% to 1.0% of water glass, and 0.06% to 0.1% of F-02 dispersant. The present invention adds ceramic waste ink to the body formula, realizes the recycling of waste ink, saves both production cost and waste ink treatment cost, and avoids the problem of serious waste of resources caused by the inability to recycle ceramic waste ink.

[0115] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A ceramic tile, characterized in that: The raw materials for the ceramic brick body include, by mass percentage: 30% to 35% of original ore mud, 33% to 38% of stone powder raw materials, 23% to 28% of medium-temperature sand raw materials, 2% to 4% of magnesia soil, 0.1% to 0.2% of ceramic waste ink, 0.8% to 1.0% of water glass, and 0.06% to 0.1% of F-02 dispersant.

2. The ceramic tile according to claim 1, characterized in that: The ceramic waste ink comprises: ceramic powder, water-soluble organic solvent, dispersant, binder and surfactant.

3. The ceramic tile according to claim 2, characterized in that: The ceramic powder includes pigment, colorant and glaze.

4. The ceramic tile according to claim 1, characterized in that: The ceramic waste ink is generated by an inkjet printing machine during the ceramic production process.

5. The ceramic tile according to claim 4, characterized in that: The ceramic waste ink is obtained by filtering impurities from waste ink produced by an inkjet printer in a ceramic production process using a 70-80 mesh screen.

6. A method for preparing a ceramic tile, characterized in that: The method comprises: According to the mass percentage, 30% to 35% of raw ore mud, 33% to 38% of stone powder raw materials, 23% to 28% of medium-temperature sand raw materials, 2% to 4% of magnesia soil, 0.1% to 0.2% of ceramic waste ink, 0.8% to 1.0% of water glass, and 0.06% to 0.1% of F-02 dispersant are mixed to prepare mud, wherein the ceramic waste ink is produced by an inkjet printing machine in the ceramic production process; The slurry is screened, iron-removed and aged, and then pumped into a spray tower for powder spraying and drying to obtain ceramic powder; the ceramic powder is screened, iron-removed and aged, and then pressed into shape to obtain a ceramic green body; Drying the ceramic green body in a drying kiln, and glazing the dried ceramic green body to obtain a glazed semi-finished green body; The semi-finished green body is fired to obtain a ceramic tile.

7. The method for preparing a ceramic tile according to claim 6, characterized in that: The moisture content of the mud is controlled at 33% to 36%, the fineness of the mud is controlled at 2.0% to 2.4% of the residue on a 325-mesh sieve, and the specific gravity of the mud is ≥1.68 g / mL.

8. The method for preparing ceramic tiles according to claim 6, characterized in that: The slurry is screened, iron-removed and aged, and then pumped into a spray tower for powder spraying and drying to obtain ceramic powder. The ceramic powder is screened, iron-removed and aged, and then pressed into a shape to obtain a ceramic green body, including: The slurry is passed through a 70-80 mesh sieve, iron removed, and aged, and then pumped into a spray tower for powder spraying and drying to obtain a ceramic powder with a moisture content of 6.8% to 7.3%, wherein the ceramic powder has a 40 mesh particle size distribution accounting for 45% to 50%; The ceramic powder is passed through a 10-16 mesh sieve, subjected to iron removal and aging treatment, and then fed into a press material distribution system through a powder feeding system for compression molding at a molding pressure of 30-32 MPa to obtain a ceramic green body.

9. The method for preparing a ceramic tile according to claim 6, characterized in that: The ceramic green body is dried in a drying kiln, and the dried ceramic green body is glazed to obtain a glazed semi-finished green body, comprising: The ceramic green body is dried in a drying kiln at a temperature of 100 to 120° C. for 50 to 60 minutes. The glaze slurry is applied on the dried ceramic green body by pouring glaze, and the performance parameters of the glaze slurry include: fineness of 325 mesh sieve residue is 0.2% to 0.4%, glaze slurry viscosity is 25 to 35 seconds, specific gravity is 1.7 to 1.8 g / mL, glaze amount is 500 to 550 g / m 2 ; The chemical components of the glaze slurry, measured by mass percentage, include: SiO2 43%~49%, Al2O3 15%~17%, CaO 3%~6%, MgO 2%~4%, BaO3%~6%, K2O1%~2%, Na2O 2%~4%, ZnO 2%~4%, ZrO2 5%~10%.

10. The method for preparing a ceramic tile according to claim 6, characterized in that: The semi-finished green body is fired to obtain a ceramic tile, comprising: The semi-finished green body is fired at a temperature of 1210-1230° C. and a firing period of 40-43 minutes to obtain a ceramic tile.

Citation Information

Patent Citations

  • Manufacturing method of ceramic tile

    CN106800422A

  • Ultra-thick black coffee full-body porcelain tile as well as preparation method and application thereof

    CN114149247A

  • Ceramic green body, ceramic tile and preparation method of ceramic green body

    CN115215633A

  • Environment-friendly experiment table ceramic panel and preparation method therefor

    WO2020052350A1

Cited By

  • High-tensile-strength ceramic green body, ceramic tile and preparation method

    CN120794598A

  • A high tensile strength ceramic body, ceramic tile and method of manufacture

    CN120794598B